Community Awareness of Building Damage Assessment After Sumedang Earthquake Disaster December 31, 2023 - Hutabarat, Lolom Evalita; Simanjuntak, Pinondang; Tambunan, Efendy; Simanjuntak, Irene Vista (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Sumedang Regency in West Java Province experienced a 4.8M earthquake on Sunday, December 31, 2023. According to the Indonesian Meteorological, Climatological, and Geophysical Agency, the earthquake occurred 2 km northeast of Sumedang Regency, West Java, at 107.94E and 6.85S. At 5 km, the epicenter was shallow. Many residential structures were rendered unworkable, with slight to serious damage. The seismic consequences also reached Garut, Cirebon, and Bandung. Understanding the geological, geophysical, and geographical features of Sumedang is important because the zoning is disaster-prone. A thorough understanding of Sumedang's geology is needed to conduct ongoing studies on fault zones, land movement analysis, building risk assessment, infrastructure stability evaluations, and sustainable development initiatives, which will affect the area's infrastructure and settlements' resilience and stability.